An evaluation of bible and theological school libraries belonging to PABATS - Villareal, Ma. Nora A.; Buenrostro, Juan Jr. C.; Manayon, Peter Jr. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1996)
This study was conducted to determine the present status of libraries of Philippine Association of Bible and Theological Schools (PABATS) and also to find out if these Bible and Theological Schools libraries belonging to PABATS conformed to its own standards which are ready for accreditation and which are not. Self-evaluation Questionnaire was the principal instrument used for gathering the data, follow-up interviews were also made.
Findings revealed that PABATS librarians were responsible in formulating the library objectives. In terms of collection, librarians in Luzon, and Mindanao agreed to have adequate circulation and reference books while those in Visayas were undecided. As for the periodicals and non-book materials, all libraries were found to be weak. Perceptions in terms of policies, shelf-reading program, faculty participation and acquisition, libraries in Luzon and Mindanao rated well while those in Visayas showed slow progress. In the organization and access to materials, libraries in Luzon and Mindanao followed the necessary requirements while libraries in Visayas were found to be in need of improvements in the area of organizing and arranging of its collection and providing sufficient indexes to periodicals. The classification system used are the Dewey Decimal Classification (DDC) and the Library of Congress Classification Scheme (LCS). Staffing patterns in PABATS libraries showed that many of them have additional duties in ministerial work in their church and respective schools. Majority operate on a one-man library system.
Most of them have bachelor's or master's degree in religion-related fields. While few are graduates of Library Science. Services offered by the libraries are circulation, inter-library loan, periodical services, reference service, and technical service. All the Bible and Theological schools are open from Monday to Friday.
The result of the assessment of Bible and Theological schools libraries facilities revealed that most have adequate physical plant, facilities, and space for readers. Areas which need improvements are books, periodicals and non-book materials.
In terms of budget allocation, Bible and Theological school libraries in Luzon and Mindanao are more privileged, where their librarians are authorized to recommend justifies and administers the library budget, which is within six percent of the total institutional budget. Libraries in the Visayas have a poor rating in terms of budget allocation. The result of evaluation in terms of working relationships with the administration revealed that libraries in Luzon and Mindanao have favorable ratings while those in the Visayas showed poor ratings.
In terms of PABATS accreditation in the area of library, seven libraries (FoBC, HMC, LTS, LNBC, MBC, PBTS, PTS) in Luzon are ready for accreditation while the other half (FBC, GBI, IBC, MCTS, PST, PUTS, WBC) are not yet ready. In Visayas, only one is qualified for accreditation (CPU) while the other four (BMABC, ETCP, NNBBC, VNBC) are not. Majority of the libraries in Mindanao (EBCS, SABC, SPBTS) are ready for accreditation while only one did not qualify (DABC).
Typescript.
Vita.
Special Problem (Master of Library Science)
Keywords: Philipine Association of Bible and Theological Schools; Theological libraries -- Philippines -- Evaluation